Pediatric Gram-negative bloodstream infections: epidemiology, antibiotic resistance, clinical outcomes and factors affecting mortality, a single center retrospective study - Yilmaz, Seyhan; Akkoc, Gulsen; Aslan Tuncay, Sevgi; Parlak, Burcu; Canizli Erdemli, Pinar; Dizi Isik, Aylin; Ergenc, Zeynep; Ilki, Arzu; Ulger Toprak, Nurver; Ergan, Bilgehan; Ocal Demir, Sevliya; Kepenekli, Eda (The Journal of Infection in Developing Countries, 2025)
Introduction: The increasing prevalence of Gram-negative bloodstream infections in pediatric patients poses significant treatment challenges, particularly from multi-drug resistant (MDR) strains. Despite advances in medical care, mortality from bloodstream infections remains a concern. Our study aims to understand pediatric patients` demographics, clinical conditions, and microorganisms causing Gram-negative infections, as well as identify factors affecting treatment outcomes and mortality. Methodology: A retrospective, observational study of Gram-negative bacteremia, including all patients < 18 years of age, hospitalized during 2022, with documented bacteremia caused by Enterobacteriaceae or non-fermentative bacteria. Results: In total 123 blood cultures from 102 patients were included study. The median age of patients was 22 months, with 85.3% having an underlying medical condition. Common strains were Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa, with 73.2% hospital-acquired infections. Among the isolated species, 28.5% were multidrug-resistant (MDR). The mortality rate was 10.5%. Mortality among patients with antibiotic-resistant isolates was 17.1%. Patients with sepsis had a markedly elevated mortality rate. Additionally, mortality was increased among patients reliant on mechanical ventilation and those with urinary catheters. Furthermore, central venous catheterization was found to be an independent predictor for sepsis (odds ratio: 2.463, 95% confidence interval: 1.095–5.53), while the presence of a urinary catheter was identified as an independent predictor of mortality (odds ratio: 5.681, 95% confidence interval: 1.142–28.249). Conclusions: The study findings highlight a critical need for strategies to reduce MDR Gram-negative infections in children, emphasizing the importance of timely removal of invasive devices and rational antibiotic use to improve patient outcomes.